Risk Assessment of Exposure to Chemical Pollutants in Industry Through the Development of a Hybrid Approach Based on Fuzzy Logic - Sadaf Jahangiri; Noushin Birjandi; Morteza Ghobadi (علوم محیطی)
Introduction: Environmental risk assessment in industrial complexes is of significant importance, as the negative impacts of these complexes pose a serious threat to the environment, human life, and international stability. This study aimed to assess the risk of exposure to chemicals and chemical incidents in industrial settings using a hybrid approach based on fuzzy logic. Material and Methods: In this study, a hybrid approach based on fuzzy logic was employed to identify, assess, and prioritize the relevant risks in the Karun oil and gas exploitation industrial zone in Ahvaz city in 1400. This method allows for more accurate and effective risk assessment by considering uncertainties and ambiguities in the data. The study included the assessment of the likelihood of hazard occurrence, the severity of hazard occurrence, the detection probability, hazard effects, risk priority number, and the necessary control measures and proposed actions. Results and Discussion: The results indicated that employees in the evaluated unit are exposed to various chemicals and chemical incidents during their activities. The risk assessment was conducted for 27 types of chemicals and 16 identified chemical incidents. Among the studied substances, exposure and contact with substances butadiene and ethylene oxide are carcinogenic for employees, and mono ethylene glycol with toxic properties causes effects on the heart and kidneys. Butanol can cause respiratory and eye issues due to negligence, leading to fire risks in the facility. The highest risk, with an RPN of 0.715, is associated with gas inhalation from the evaporation of hydrofluoric acid and nitrogen. In contrast, the lowest risks, with RPNs below 0.1, are related to two liquid leakage scenarios at ambient temperature and pressure. The results of the risk assessment calculation show that none of the substances in the company have a very high risk for the employees, but five substances, naphtha, ammonia gas, acetic acid, chlorine gas, and methanol, have a high risk for the employees. The overall risk assessment results for exposure to chemicals and chemical incidents showed that a significant portion of the industry's activities falls within the high-risk range, highlighting the necessity for increased attention and planning to reduce this risk level to prevent serious incidents. Additionally, the results demonstrated that using a systematic fuzzy analysis method provides significant improvements in risk management and can be utilized as an effective tool in this field. Conclusion: Based on the results, risk assessment using a hybrid approach based on fuzzy logic can aid decision-makers in improving environmental performance and creating safer and more sustainable conditions for the industry. By utilizing information related to hazards and the results of measurements and evaluations of chemical factors within the framework of chemical pollutant exposure risk assessment, various jobs can be ranked in terms of exposure to harmful chemical factors. These results can be used to prioritize resource allocation for implementing control measures and reducing exposure risk to an acceptable level.